Low-frequency high-temperature internal friction in Ti-13Nb-13Zr alloy - Niemeyer, T. C. [UNESP]; Grandini, Carlos Roberto [UNESP]; Schneider, S. G. (My University, 2006)
Recent studies have been done to achieve biomedical alloys containing non-toxic elements and presenting low elastic moduli. It has been reported that Ti-Nb-Zr alloys rich in beta phase, especially Ti-13Nb-13Zr, have potential characteristics for substituting conventional materials such as Ti-6Al-4V, stainless steel and Co alloys. The aim of this work is to study the internal friction (IF) of Ti-13Nb-13Zr (TNZ) alloy due to the importance of the absorption impacts in orthopedic applications. The internal friction of this alloy produced by arc melting was measured using an inverted torsion pendulum with the free decay method. The measurements were performed from 77 to 700 K with heating rate of 1 K/min, in a vacuum better than 10-5 mBar. The results show a relaxation structure at high temperature strongly dependent on microstructure of the material. Qualitative discussions are presented for the experimental results, and the possibility of using the TNZ as a high damping material is briefly mentioned.
Keywords: Anelasticity; High damping; Internal friction; Ti alloys; Free decay method; Heating rate; Cobalt alloys; Damping; Elastic moduli; Elasticity; Stainless steel; Titanium alloys